It's all about mechanisms – what process-tracing case studies should be tracing. Issue 5 (2nd September 2016) - Beach, Derek
ABSTRACT: Process-tracing (PT) as a distinct case-study methodology involves tracing causal mechanisms that link causes (X) with their effects (i.e. outcomes) (Y). We trace causal mechanisms whereby a cause (or set of causes) produces an outcome to both: (1) make stronger evidence-based inferences about causal relationships because the analysis produces within-case evidence of each step of the causal process (or absence thereof) in between a cause and outcome, and (2) because tracing mechanisms gives us a better understanding of how a cause produces an outcome. Yet, when we look at the methodological literature on PT, there is considerable ambiguity and discord about what causal mechanisms actually are. The result of this ambiguity and discord about what mechanisms are clearly maps onto existing applications of PT, with most PT case studies completely ignoring the underlying theoretical causal processes. In the few PT applications where mechanisms are unpacked, they are typically only developed in a very cursory fashion, with the result that there is considerable ambiguity about what theoretical process the ensuing case study actually is tracing. If we want to claim we are tracing causal mechanisms, the causal processes in between X and Y need to be unpacked theoretically. How can we claim we are tracing a causal 'process' when we are not told what the process (i.e. mechanism) actually is? To alleviate this problem, the article attempts to develop a clearer definition of causal mechanisms to provide scholars with a framework for theorising mechanisms in a fashion that is amenable to in-depth empirical analysis using PT.